COBIT principles to govern flood management - Othman, Marini; Ahmad, Mohammad Nazir; Suliman, Azizah; Arshad, Noor Habibah; Maidin, Siti Sarah (Elsevier, 2014)
The worsening condition in Malaysia needs improvement In all aspects of flood management. Improvement on the governance of information and information related technology prevalent to flood could promote better planning and decision making in alleviating the problems arising from the disaster.This article seeks to propose a look into COBIT as an approach to address the issues related to flood management. The COBIT framework, which has been widely accepted and used in business enterprises, can be adapted to govern natural disaster management projects by having well-defined governance over processes, the required information and related information technology. A qualitative field study is employed in the identification of challenges of managing information and information related technology in flood management. The COBIT structure is used as a reference in identifying components necessary in a flood management governance framework. In doing so, a flood cycle is first established: process and activities involved in flood management are sequenced into phases which reflect a flood cycle. Then, goals for each of the phases in the lifecycle are set. A general structure comprising of roles and enablers to govern the cycle is then outlined. As a result, this paper proposed a high level governance framework which focused on the information and information-related technology whilst considering the collaborative environment in the effort of managing flood. An application of COBIT, it's principles and processes to govern flood management projects is discussed within the context of flood disaster in Malaysia.